2015
DOI: 10.1007/s10534-015-9845-9
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical properties of the new generation IV iron preparations ferumoxytol, iron isomaltoside 1000 and ferric carboxymaltose

Abstract: The advantage of the new generation IV iron preparations ferric carboxymaltose (FCM), ferumoxytol (FMX), and iron isomaltoside 1000 (IIM) is that they can be administered in relatively high doses in a short period of time. We investigated the physico-chemical properties of these preparations and compared them with those of the older preparations iron sucrose (IS), sodium ferric gluconate (SFG), and low molecular weight iron dextran (LMWID). Mössbauer spectroscopy, X-ray diffraction, and Fe K-edge X-ray absorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 53 publications
3
86
1
1
Order By: Relevance
“…This is consistent with studies on labile-free iron release of different preparations, showing the lowest levels with FCM [113]. Because of its high stability, FCM can be quickly administered at high dose, up to 1000 mg of elemental iron in 15 min [114].…”
Section: The Newer IV Iron Preparationssupporting
confidence: 90%
“…This is consistent with studies on labile-free iron release of different preparations, showing the lowest levels with FCM [113]. Because of its high stability, FCM can be quickly administered at high dose, up to 1000 mg of elemental iron in 15 min [114].…”
Section: The Newer IV Iron Preparationssupporting
confidence: 90%
“…They can be classified as non-dextran-derived and dextran-derived complexes depending on their carbohydrate shell. In non-dextran-derived complexes, such as ferric carboxymaltose, a higher molecular weight leads to a more stable complex and lower labile iron release [29, 34]. In dextran-derived complexes, however, there is no correlation between complex stability and molecular weight [29, 34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Iron in a free state might be leading to anaphylactic-like symptoms or might be the reason for the skin erythema in one of the patients (34). However, a recently published study shows that if applied according to recommendations, only a minimum of free iron emerges from ferumoxytol during intravenous injection (35) and that this amount of free iron should not have any clinical relevance (36). A previous study showed that high-rate, high-volume administration of iron-carbohydrate compounds can lead to hypotension, nausea, back and chest pain through complement activation by labile iron (37).…”
Section: Discussionmentioning
confidence: 99%